The 2nd Baltic Osseointegration Academy and Lithuanian University of Health Sciences Consensus Conference 2019. Summary and Consensus Statements: Group II - Extraction Socket Preservation Methods and Dental Implant Placement Outcomes within Grafted Sockets - Pablo Galindo-Moreno; Fernando Suárez López del Amo; Ricardo Faria-Almeida; Bruno Leitão Almeida; Inesa Astramskaite-Januseviciene; Shayan Barootchi; Tiago Borges; André Correia; Francisco Correia; Jad Majzoub; Miguel Padial-Molina; Mindaugas Pranskunas; et al. (eJournal of Oral Maxillofacial Research, 2019)
Introduction: The task of Group II was to review and update the existing data concerning extraction socket preservation with or without membranes and soft tissue influence on post-extraction alveolar ridge preservation; extraction socket preservation using different biomaterials as bone grafts, growth factors, and stem cells. Special interest was paid to the dental implant placement outcomes within grafted sockets.